Strategi Marketing Desa Wisata Berbasis Informasi dan Teknologi - Ridha Afina; Hagia Qatrunnada; Harfinolla Amabel Kirani; Woro Harkandi Kencana; Sularso Budilaksono; Febrianty Febrianty; Devita Gantina (IKRAITH-Teknologi, 2022)
Tourism villages were formed to empower the community so that they can act asdirect actors in an effort to increase readiness and concern in responding to tourism potential ortourist attraction locations in each village. The objects of this research are 3 tourist villages inDKI Jakarta, namely: Betawi Cultural Village Tourism Village, Untung Jawa Island TourismVillage and Bhinneka Eduwisata Village Tourism Village. The purpose of this study is todetermine the IT-based marketing strategy used by tourism villages in DKI Jakarta. This studyuses AISAS theory consisting of Attention (attention), Interest (interest), Search (search), Action(action), and Share (sharing). AISAS explains the occurrence of significant changes in consumerbehavior patterns since the advent of technology. The research method uses a descriptiveapproach. The data collection technique is by exploring the tourist village managers and visitorsand observing the tourist villages and the digital platform used. In this study, the marketingstrategy used by the tourist village is in the form of a website platform, social media and mobileapplications. The tourist villages of Untung Jawa Island and Betawi Village use the potential ofthe three platforms, while the Bhinneka edutourism village has not maximized the use ofmarketing using digital platforms.